Original article HDR and PDR 192Ir source activity control procedures, as the part of the quality assurance system at Brachytherapy Department of Greater Poland Cancer Centre - Zwierzchowski, Grzegorz; Błasiak, Barbara; Stefaniak, Patrycja; Bielęda, Grzegorz (Journal of Contemporary Brachytherapy, 2009)
Purpose: One of the main causes of treatment failures in brachytherapy is incorrect source strength specification in planning system or treatment delivery console. Source strength control is the only scheme to avoid such mistakes. The main aim of this work was to present results of three years of HDR and PDR sources activity control. Material and methods: Study was based on data from 14 192Ir HDR and PDR sources exchanges. Sources were checked three times: at the exchange day and after one and two months. Measurements were performed twice with thimble chamber (PMMA phantom), and well chamber. The source strength were measured as air – kerma and recalculated to activity. Results: Source activities measured using well chamber and thimble chamber, as well as activities provided by planning system, were presented for PDR and HDR, respectively. Differences between results obtained using each chamber and activities from planning system were presented graphically. The calculated and measured activities differed less than 5%. Wilcoxon test was performed as well, no statistically significant differences were observed among HDR or PDR activities. Conclusions: Checking of source parameters is one of the most important parts of quality control system in brachytherapy facilities. Well chamber and thimble chamber based dosimetry systems are fast and reliable tools for 192Ir source parameters checking in working brachytherapy department conditions.